Lexicon-Based Sentiment Analysis of Indonesian Language Student Feedback Evaluation - Firdaus, Raginda; Asror, Ibnu; Herdiani, Anisa (Indonesian Journal on Computing (Indo-JC), 2021)
Student feedback for lecturer plays an important role, it used to improve the quality of lecturer in teaching. In general, student feedback consists of two types, quantitative feedback and qualitative feedback. For quantitative feedback, it can easily analyze using statistical calculations, because it contains closed questions with multiple choices. But for qualitative feedback, it is difficult to analyze, because it contains open questions with essay answers. Lecturers can analyze manually, but it takes extensive times and the results can be very subjective. To overcome this problem, sentiment analysis is applied to analyze textual data automatically in order to improve teaching evaluations. This research uses student feedback as dataset, and lexicon approach with InSet Lexicon. In this research, the evaluation result shows that system accuracy is 90.9%.